Loneliness Among First-Year Out-of-Town College Students: How Is It Related to Personality Trait? - Hutabarat, Tabita Sammasda; Rahayu, Maria Nugraheni Mardi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Students will migrate and move temporarily from their hometown to continue their education at a higher level while learning to live independently from their parents. During the migration process, students will be faced with various challenges, one of them is loneliness. This study aims to determine the relationship between each trait in the Big Five Personality with loneliness experienced by first-year out-of-town students. This study is a quantitative study with an accidental sampling method and the participants were 211 first-year out-of-town students of Satya Wacana Christian University. This study uses the 6-Items Cross-Cultural Social Isolation Scale to measure loneliness and the Big Five Inventory-2 Short (BFI2-S) to measure personality. The results showed that there was a negative relationship between trait conscientiousness (p=0.000, r=-0.252), trait extraversion (p=0.000, r=-0.302), and trait agreeableness (p=0.028, r=-0.132) with loneliness. In addition, there is a positive relationship between trait neuroticism (p=0.000, r=0.398) and loneliness. Meanwhile, no relationship was found between trait openness to experience (p = 0.060 and r = -0.107) and loneliness. The findings emphasize that students can participate in various activities that allow them to interact with others and establish healthy interpersonal relationships that help prevent loneliness.Mahasiswa akan merantau dan berpindah sementara waktu dari kampung halamannya untuk melanjutkan pendidikan pada jenjang yang lebih tinggi sekaligus belajar untuk hidup mandiri dari orang tua. Selama proses merantau, mahasiswa akan dihadapkan dengan berbagai tantangan salah satunya yaitu kesepian. Penelitian ini bertujuan untuk mengetahui hubungan antara masing-masing trait dalam big five personality dengan kesepian yang dialami oleh mahasiswa rantau tahun pertama. Penelitian ini merupakan penelitian kuantitatif dengan metode accidental sampling dan partisipan dalam penelitian ini adalah 211 mahasiswa rantau tahun pertama Universitas Kristen Satya Wacana. Adapun alat ukur yang digunakan dalam penelitian ini yaitu 6-Items Cross Cultural Social Isolation Scale untuk mengukur kesepian dan Big Five Inventory-2 Short (BFI2-S) untuk mengukur kepribadian. Hasil penelitian menunjukkan bahwa terdapat hubungan negatif antara trait conscientiousness (p=0,000, r=-0,252), trait extraversion (p=0,000, r=-0,302), dan trait agreeableness (p=0,028, r=-0,132) dengan kesepian. Selain itu, terdapat hubungan positif antara trait neuroticism (p=0,000, r=0,398) dengan kesepian. Sementara itu, tidak ditemukan hubungan antara trait openness to experience (p = 0,060 dan r = -0,107) dengan kesepian. Temuan ini menekankan agar mahasiswa dapat mengikuti berbagai kegiatan yang membuat mahasiswa dapat berinteraksi dengan individu lain dan menjalin relasi interpersonal yang sehat sehingga membantu mencegah munculnya perasaan kesepian.